The suburban captivity of the church : contextualising the gospel for Post-Christian Australia - Foster, Tim (Moreland, VIC : Acorn Press, 2014)
For far too long, Australian evangelicals have proclaimed a gospel loaded with the cultural baggage of suburbia: personal security, individual salvation and an other-worldly focus. Is this message really a set of timeless truths with universal application? Or have we injected Jesus' message with our own values?The Suburban Captivity of the Church calls us to venture beyond the picket fence and engage with the cultural narratives around us, to see how God's big story meets them with both challenge and hope. Whether we are reaching a new culture, or trying to bring the gospel to our own in a more biblically faithful way, this book will equip us for the task.
Includes bibliographical references.
Keywords: Bible -- Theology; Bible -- Theology; Christianity and culture; Australia -- Religious aspects -- Christianity; Australian